Mathematical Literacy Reviewed from Student’s Metacognition On the PJBL Learning with RME Approach Assisted Edmodo - Ahadi, Faiz Al; Asikin, Mohammad; Wardono, Wardono (Universitas Negeri Semarang, 2021)
This study aims to find patterns in the learning of mathematics literacy skills on the PJBL learning with RME approach assisted edmodo reviewed from student’s metacognition. This type of research is concurrent mixed methods. The study design non-equivalent (pretest-posttest) Control Group Design. The data collection technique by using tests, observation, documentation, and interviews. This research subject is class VII N 36 Semarang. Based on the results that the mathematics literacy skills reviewed from students' metacognition are distinct, that students with higher mathematical literacy skills has 5 students with high category metacognition, 8 students with medium category metacognition. Students with medium mathematical literacy skills has 4 students with high category matecognition, 8 students with medium category metacognition and 1 student with low category metacognition. Furthermore, students with low category mathematical literacy skills has 5 students with low category metacognition.